Developing mobile-based project-based learning module for project management courses in vocational education - Sarwandi Sarwandi; M Giatman; Sukardi Sukardi; Dedy Irfan (Jurnal Pendidikan Vokasi, 2019)
The purposes of this research were (1) to design and implement the development of mobile-based e-modules, (2) to know the students' and lecturers' responses toward the development of the mobile-based e-modules, and (3) to know the students' learning outcomes after using the mobile-based e-modules. The research employed a Research and Development with the 4D development model. The participants of this study were 54 students and three lecturers of construction engineering education. The data on the students' and lecturers' responses to the development of mobile-based e-modules were obtained using the questionnaire method. The results of the study show that the design and implementation of the developed mobile-based e-modules were successful based on several tests conducted. The successfully developed e-modules can be seen from the students' responses, in which 64% are included in the Very Practical category, and only 36% are in the Practical category. On the other hand, the results of the lecturers' responses show a Very Practical category by the percentage of 100%. As a consequence, the students' learning outcomes are declared complete at 100% and increase with a gain score of 0.44 (moderate) from 54 students in the project management course.